(untitled) (Third Sector Social Economic Review, 2013)
The criterions abaout brand eguity can measure with financial discipline or marketing discipline. There is a important point at the contemporary marketing activity for the customer orientation elements which enrich to the brands have to evalute with a perpective of customer orientation. The personality and identity which the brand has, effect awareness and association dimensions These image and awerness will be a brand valuable or not. When a brand is valuable, this time the firms want to extand their brands. Brand equity will form over again with the results of brands extensions This study was workouted to determine the dimesions of brands effect brand equiy or not, the brand equity effect the decision of brand extensions or not and how the brand extensions effect brand equity.